De la réification à l'autonomie, les difficultés à penser sociologiquement le travail collectif des enseignants - Nicolas Sembel (Université de Provence, 2014)
Our approach of teachers' collective work is decidedly sociological. Starting from both the informal work of the interactionnist sociology and reified work of marxist sociology and certain of its current developments, thus combining perspectives "micro-empirical" and "macro-history", we will show how some professional contexts, through with conflicting logics of deskilling et re-intellectualization of teacher's work, can be enlightened by the sociological analysis of this work. Our main result is the difficulty of teachers to formalize, individually and collectively, the deskilling and the reification of their work; the main way out of this cul-de-sac is a double action towards "meso-organizational" and "socioanalytical collective" levels, which remain largely to implement, and are, according to us, the conditions for a professional autonomy, which is necessary for the collective work.